How do you go to the bathroom in space? - Pogue, William R. (New York : Tom Doherty Associates, 1999)
Answers questions about the day-to-day details of living in space, including what it feels like to be weightless, how food is cooked, and what happens to the body in space.
Includes bibliographical references (p. 209-215) and index.
Books for the Teen Age (NYPL).
Young Adult.
Young Adult
Keywords: Pogue, William R. -- Anecdotes; Pogue, William R. -- Anecdotes; Astronautics -- Miscellanea; Astronautics -- Miscellanea